2003
DOI: 10.1128/aac.47.10.3275-3280.2003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Multiple- or Single-Dose Cidofovir against Vaccinia and Cowpox Virus Infections in Mice

Abstract: Orthopoxviruses, including variola and monkeypox, pose risks to human health through natural transmission or potential bioterrorist activities. Since vaccination has not recently been utilized for control of these infections, there is renewed effort in the development of antiviral agents not only for postexposure smallpox therapy but also for treatment of adverse reactions following vaccination. The objectives of this study were to expand on the results of others that cidofovir (CDV) is effective in mice inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 25 publications
1
67
0
Order By: Relevance
“…Otherwise, the type of infection in mice resulting from the 50-μl i.n. challenge with the SF strain of cowpox virus is similar to the infection with the typical cowpox virus strain [1,5,6].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Otherwise, the type of infection in mice resulting from the 50-μl i.n. challenge with the SF strain of cowpox virus is similar to the infection with the typical cowpox virus strain [1,5,6].…”
Section: Discussionmentioning
confidence: 66%
“…The drug treatment regimen used in the present investigations involved two consecutive days of treatment, as was done previously [7,9]. Other investigators have reported using lower daily doses of the compound, but by administering it for more consecutive days against poxvirus infections [5]. The shorter term of treatment mimics the one that will likely be given to humans, since the drug must be administered intravenously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cidofovir (CDV) and cyclic CDV (cCDV) have been shown to be potent inhibitors of poxvirus replication in vitro (1,7,8,13) and in animal model studies (5,10,12); however, these compounds are inactive when given orally.…”
mentioning
confidence: 99%
“…Cidofovir is a potent antiviral drug that is currently being investigated for treating deadly smallpox (variola) and monkeypox, although it is licensed for human immunodeficiency virus-associated cytomegalovirus retinitis (1,5,26,31). Given the possibility that cidofovir or other antiviral drugs can limit initial active vaccinia virus replication, cidofovir and Dryvax (cidofovirϩDryvax) coadministration may reduce Dryvax-mediated vaccination complications.…”
mentioning
confidence: 99%